Improving methods of prospective life cycle assessment for wastewater treatment process development and selection - Högstrand, Sofia ; 0000-0001-6552-679X (Department of Process and Life Science Engineering, Lund University., 2025)
Future-oriented environmental assessments—in particular, prospective life cycle assessments (LCAs)—are increasingly applied within the wastewater treatment (WWT) sector. This thesis contributes to this field of research by addressing how to estimate the environmental impact (improving LCA methodology) and what the impact amounts to (WWT-specific results) for a wastewater treatment plant not yet constructed. To this end, four case studies were performed, resulting in the four accompanying papers. Regarding LCA methodology, this thesis shows that it is possible to simplify the system by narrowing the system function to reduce the need for data while still maintaining relevance—e.g., by delimiting the technological system while using a simplified model to account for impacts on the larger system. It also shows the extent of which pilot plants and dynamic models are useful for creating data inventories when accounting for differences in scale and model uncertainties, respectively. Furthermore, the thesis demonstrates that alternative impact assessment approaches, such as the application of bioassays rather than conventional chemical analysis, can capture missing aspects of toxicity. However, further research on important parameters—such as choice of reference substances, types of bioassays and biological endpoints—is necessary to aid interpretation and increase the meaningfulness. As for WWT-specific results, the thesis describes the hotspots and the desirable paths forward for processes for nutrient removal (biological and chemical phosphorus removal) and recovery (NPHarvest, struvite precipitation, biochar production, and sludge stabilisation), as well as micropollutant removal (biological and mechanical post-treatment after ozonation). Moreover, the thesis demonstrates how prospective LCA is an important tool for WWT process development and selection to portray environmental aspects and facilitate improved decision-making.
Keywords: Environmental assessment; Enhanced biological phosphorus removal (EBPR); Nutrient recovery; Quaternary treatment; Sludge management; Bioassay